Thrombocytosis and CA125 as Predictor of Malignancy in Gynaecological Pelvic Mass - Miran, Najmah M. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Pelvic masses are common in women & can present at any age of woman life, it could be benign or malignant mass and may originate from gynecological organs like cervix, uterus, uterine adnexia, or from other pelvic organs like intestine, bladder, ureters, skeletal muscle, and bone. Objective: We attempted to determine the increasing of platelet counts(> 450.000 /micro liter) and CA125serum level (> 35 U/mL) as useful tools for predicting and confirming malignancy in gynecological pelvic mass. Patients and methods: A prospective unmatched hospital based case-control study carried out at Baghdad Teaching Hospital, about 126 women were enrolled in our study, divided into two groups 60 women were control group (free of gynecological pelvic mass). The other group includes 66 women above 15 years old with gynecological pelvic mass were all candidate for laparotomy. Results: Serum CA125 and blood platelets count were tested for validity when used as a test to predict a diagnosis of malignancy in gynecological pelvic mass differentiating it from benign gynecological pelvic mass. Both tests showed a very high validity in diagnosis, with serum CA125 showing a marginally higher validity. All studied subjects with a blood platelets count ≥ 385.000 and CA 125≥ 41.7were malignant, while everybody below this cut-off value was benign or healthy. Conclusion: Both blood platelet count (≥385 X 103microlitter) &serum level of CA125 (≥41.7 U/mL) are useful predictor tools to confirm malignancy in gynecological pelvic mass.